Mengungkap Penghindaran Pajak Perbankan Dari Profitabilitas, Leverage, dan Ukuran Perusahaan - Virda Kunto Tri Atmojo; Sugiarti Sugiarti; Faiz Rahman Siddiq (Jurnal Bisnis dan Kewirausahaan, 2024)
The aim of this research is to determine the influence of profitability, debt levels and company size on tax avoidance practices. This research is a type of quantitative research by conducting hypothesis testing. The research design uses associative research, namely to find out whether there is a relationship between two or more variables. The research population is all companies listed on the Indonesia Stock Exchange (BEI). The samples were taken from 10 banking companies taken using purposive sampling technique. The required data is obtained from the company website or from the Indonesian Directory Exchange (IDX). Data analysis techniques use classic assumption tests and multiple regression analysis, F test, R2 test, and t test. The research results show that: (1) Profitability (ROA) statistically has a negative effect on CETR. The higher the level of profitability, the lower the CETR (which means the higher the level of tax avoidance). (2) Leverage (DER) statistically has a negative effect on CETR. The higher the level of leverage, the lower the CETR (which means the higher the level of tax avoidance). (3) Company size has no effect on tax avoidance. Company size has no impact on tax avoidance activities.